Exploring leadership for college students who want to make a difference - Komives, Susan R. 1946- (Jossey-Bass, 1998)
Exploring Leadership provides a unique view of leadership as a participatory process, and helps students and young adults to develop their own potential for leadership in the organizations, groups, and communities of an increasingly diverse and complex world.